The Novel MoS2/MnO2–BSA Nanocomposite Significantly Enhances Antitumour Efficacy through Synergistic Photothermal Therapy/Hemodynamic Therapy - Lingle Zhang; Xiaoqing Qian; Yingying Yang; Tingting Xiang; Jinrong SiTu; Hongzhang Yan; Kai Yang (Nano Biomedicine and Engineering)
Cellular photothermal and chemical kinetic therapy has recently been acknowledged as an effective cancer treatment method. Photothermal therapy (PTT) works by transforming light energy into heat through the photothermal effects triggered by near-infrared (NIR) laser exposure. The employment of nanomaterials as carriers for PTT agents or as PTT agents themselves offers improved therapeutic outcomes with fewer side effects through enhanced photothermal conversion efficiency, accumulation of the PTT agents in the tumor tissue. In this work, we synthesized new MoS2/MnO2 nanomaterials modified with bovine serum protein to enhance the effectiveness of the Fenton-like reaction between MoS2 and MnO2 to produce •OH through photothermolysis excitation using a near-infrared (NIR) 808 nm laser. In vitro measurements further confirmed the exceptional ability of MoS2/MnO2–modified bovine hemoglobin (BSA) to destroy cancer cells. We believe that photothermal therapy can offer new insights into cancer therapy and greatly enhance the efficacy of chemotherapeutic tumor treatments.